The Effect of Adding Transcranial Direct Current Stimulation to Hyperbaric Oxygen Therapy in Patients With Delayed Encephalopathy After Carbon Monoxide Poisoning: A Randomised Controlled Trial - Cao, Huifang; Tan, Xiaona; Liu, Zibo; Zhao, Long; Chi, Lin; Li, Manyu; Liu, Chunhui; Li, Hongling (Frontiers in Neurology, 2021)
Objective: To investigate the effect of transcranial direct current stimulation (tDCS) combined with hyperbaric oxygen therapy (HBOT) in patients with delayed encephalopathy after carbon monoxide poisoning (DEACMP). Design: A parallel-group, open-label randomised controlled study. Setting: Hyperbaric Oxygen Therapy Room of the Second Hospital of Hebei Medical University. Subjects: A total of 40 patients were recruited for the current study. Patients were randomly divided into a treatment group and a control group (20 cases/group). Interventions: Control group: conventional, individualised rehabilitation therapy. Treatment group: conventional, individualised rehabilitation therapy and tDCS. Main measures: cognitive function of patients, the Barthel Index (BI). Results: After treatment, significantly higher MMSE and BI scores, as well as a greater reduction in P300 latency and an increase in P300 amplitude, were observed in the treatment group compared to the control group (MMSE: 13±7 vs. 9±5; P300 latency: 342±29 vs. 363±17 ms; P300 amplitude: 7.0±3.3 vs. 5.1±2.7 μV; all P<0.05). In both groups, however, MMSE and BI scores, in addition to P300 amplitude, were significantly improved; in contrast, there was a decrease in P300 latency in both groups after treatment compared to before treatment (all P<0.05). Conclusion: Combined with HBOT, tDCS can help improve cognitive function and ADL in patients with DEACMP. This combination therapy might be a helpful method to enhance the recovery of patients with DEACMP.